2022
DOI: 10.1007/s40894-022-00179-4
|View full text |Cite
|
Sign up to set email alerts
|

How the Exposure to Beauty Ideals on Social Networking Sites Influences Body Image: A Systematic Review of Experimental Studies

Abstract: Sharing and viewing photos on social networking sites (SNSs) have been identified as particularly problematic for body image. Although correlational research to date has established that SNS use is associated with increased body dissatisfaction, only experimental studies can enhance confidence in the conclusions drawn. For this reason, this systematic review synthesizes data from 43 experimental studies (N = 8637; %F = 89.56; mean age = 21.58 ± 1.78) examining the effect of viewing idealized images (i.e., attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 90 publications
0
32
0
2
Order By: Relevance
“…A mediating role of body dissatisfaction in the relationship between PIU and different psychopathological outcomes including loneliness, depression, anxiety, and social anxiety was evidenced by a previous recent study [28]. Additionally, previous systematic reviews [11,12], indicated appearance-based social comparison as one of the main explaining mechanisms of the negative effect of SNSs use on body image. According to social comparison theory, individuals tend to compare their opinions and abilities with others' opinions and abilities [31].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…A mediating role of body dissatisfaction in the relationship between PIU and different psychopathological outcomes including loneliness, depression, anxiety, and social anxiety was evidenced by a previous recent study [28]. Additionally, previous systematic reviews [11,12], indicated appearance-based social comparison as one of the main explaining mechanisms of the negative effect of SNSs use on body image. According to social comparison theory, individuals tend to compare their opinions and abilities with others' opinions and abilities [31].…”
Section: Introductionmentioning
confidence: 85%
“…The negative in uence of using and being exposed to SNSs on body image has been recently evidenced by an emerging body of research. Speci cally, a wide number of studies have found that SNS use is associated with body dissatisfaction and disorderly eating among young women and men [for a systematic review, see 11,12; for a meta-analysis, see 13]. Internalization of beauty ideals, appearance-based comparison and self-objecti cation were found to explain the detrimental effect of SNS use on body image [11], providing support for both the social comparison [7] and objecti cation theory (i.e., internalization of an observer's perspective as the primary view of the physical self) [14] in the eld of SNSs.…”
Section: Introductionmentioning
confidence: 99%
“…1 Faculty of Public Health & Policy, London School of Hygiene and Tropical Medicine, London, UK. 2 School of Nursing and Health Studies, University of Washington Bothell, Bothell, WA, USA.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…In addition, the intensive use of SNSs could reduce self-concept clarity [60]. Recent literature [57,61] has also shown gender differences in online self-presentation: female adolescents were likely to modify their online selfpresentation by editing their photos, which led to lower selfacceptance, including reduced body and life satisfaction [10,62]. Indeed, SNSs make online social status comparisons easier, with negative emotional consequences [63], regardless of explicit negative comments [64].…”
Section: Adolescents' Online Self-presentation and Social Comparisonmentioning
confidence: 99%